Polycomb repressive complex 1.1 coordinates homeostatic and emergency myelopoiesis - Nakajima-Takagi, Yaeko; Oshima, Motohiko; Takano, Junichiro; Koide, Shuhei; Itokawa, Naoki; Uemura, Shun; Yamashita, Masayuki; Andoh, Shohei; Aoyama, Kazumasa; Isshiki, Yusuke; Shinoda, Daisuke; Saraya, Atsunori; et al. (eLife, 2023)
Polycomb repressive complex (PRC) 1 regulates stem cell fate by mediating mono-ubiquitination of histone H2A at lysine 119. While canonical PRC1 is critical for hematopoietic stem and progenitor cell (HSPC) maintenance, the role of non-canonical PRC1 in hematopoiesis remains elusive. PRC1.1, a non-canonical PRC1, consists of PCGF1, RING1B, KDM2B, and BCOR. We recently showed that PRC1.1 insufficiency induced by the loss of PCGF1 or BCOR causes myeloid-biased hematopoiesis and promotes transformation of hematopoietic cells in mice. Here we show that PRC1.1 serves as an epigenetic switch that coordinates homeostatic and emergency hematopoiesis. PRC1.1 maintains balanced output of steady-state hematopoiesis by restricting C/EBPα-dependent precocious myeloid differentiation of HSPCs and the HOXA9- and β-catenin-driven self-renewing network in myeloid progenitors. Upon regeneration, PRC1.1 is transiently inhibited to facilitate formation of granulocyte-macrophage progenitor (GMP) clusters, thereby promoting emergency myelopoiesis. Moreover, constitutive inactivation of PRC1.1 results in unchecked expansion of GMPs and eventual transformation. Collectively, our results define PRC1.1 as a novel critical regulator of emergency myelopoiesis, dysregulation of which leads to myeloid transformation.
Keywords: hematopoietic stem; progenitor cell; polycomb repressive complex 1.1; myelopoiesis; emergency myelopoiesis